2019
DOI: 10.1007/s11159-019-09793-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-directed learning: A fundamental competence in a rapidly changing world

Abstract: Self-directed learning is a fundamental competence for adults living in our modern world, where social contextual conditions are changing rapidly, especially in a digital age. The purpose of the present article is to review key issues concerning self-directed learning in terms of (1) what are the historical foundations of the self-directed learning concept?; (2) who may benefit from self-directed learning?; (3) who is likely to carry it out?; and (4) what does research show regarding outcomes of the self-direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
112
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(126 citation statements)
references
References 46 publications
9
112
0
5
Order By: Relevance
“…Overall, the student reflective comments provided insight into how this activity affected their SDL abilities beyond what we could observe by simply grading their assignments. The students' reflections revealed that we should not assume all of our medical students matriculate with well-developed selfdirected learning skills, an observation which is consistent with the SDL literature [4,6,20,25].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Overall, the student reflective comments provided insight into how this activity affected their SDL abilities beyond what we could observe by simply grading their assignments. The students' reflections revealed that we should not assume all of our medical students matriculate with well-developed selfdirected learning skills, an observation which is consistent with the SDL literature [4,6,20,25].…”
Section: Discussionsupporting
confidence: 66%
“…The theoretical literature of SDL in adults [4,6,42] and the evolving literature on SDL in medical education [43][44][45] describe multiple dimensions of SDL including (1) management of learning skills, (2) personality characteristics of the learner, (3) the learning environment, and (4) the metacognitive process [6,46,47]. The results of our study build on this literature by showing that our students' perceptions of how they approach SDL mirror these dimensions.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Individuals with self-directed learning skills can manage themselves to acquire knowledge and comprehend how to resolve problems. Self-directed learning is a fundamental competence for individuals living in our modern world, where social contextual conditions are changing rapidly, especially in a digital age (Karatas & Zeybek, 2020;Morris, 2019). Self-directed learners are often more actively involved in learning tasks, such as reading online learning materials, planning and evaluating learning milestones (Geng et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, self-directed learning skills were extracted as the one of the competencies for academic nurse educator in this study, although the Nurse Educator Core Competencies (WHO, 2016) has not been clearly indicated. Having self-directed learning skills as adult learners is an important competency for academic educators (Lopes & Cunha, 2017; Morris, 2019). In contrast to the Nurse Educator Core Competencies (WHO, 2016), this study showed that both personal and professional individual traits and values were components constituting competency in academic nurse educators.…”
Section: Discussionmentioning
confidence: 99%